Realising long-term transitions towards low carbon societies: Impulses from the 8th Annual Meeting of the International Research Network for Low Carbon Societies - Stefan Lechtenböhmer; Katharina Knoop (Wuppertal Institut für Klima, Umwelt, Energie, 2017)
In spite of current multiple political crises, global warming will remain a prime issue on the global agenda. The adoption of the Paris Agreement in 2015 and its quick ratification in 2016 have created a strong momentum for worldwide action against climate change. As global greenhouse gas emissions must decline towards levels close to zero by the middle of the century, the rapid decarbonisation of energy systems is high on the agenda of most countries around the globe. This publication delivers insights into cutting edge research on the necessary transitions towards low carbon societies and by this aims to contribute to international as well as national policymaking. The topics covered in more than 20 concise original articles are among the most important issues for progressing solutions for climate change and sustainable development. The papers discuss recent findings and case studies in the following subject areas: Governance of the necessary long-term transitions in the context of potential known and unknown adverse developments ; Policy instruments and strategies that allow for financing the transition to low carbon economies and, at the same time, respond to today's economic and social challenges ; Integrated strategies for three of the most important arenas of global decarbonisation: Cities, as much of the change and necessary investment for low carbon societies must take place, be planned, be financed and be built in cities; industry, particularly the energy-intensive processing industries, which are at the core of society's metabolism and are responsible for a large and growing share of global emissions and science as a whole, which must become more solutions-oriented because the transitions needed will rely heavily on research providing solutions for technological as well as societal problems. As a contribution to these great challenges and at the request of the G7 Environment Ministers, the Low Carbon Society Research Network (LCS-RNet) acts as a forum aimed at fostering research and policymaking to jointly achieve decarbonised energy systems in countries around the world. It convenes leading scientists, practitioners and policymakers and aims at supporting governments in proceeding jointly towards the design and implementation of climate-friendly low carbon societies. – – Trotz vieler aktueller politischer Krisen wird der Klimawandel ein Hauptthema auf der internationalen Agenda bleiben. Die Verabschiedung des Übereinkommens von Paris in 2015 und seine schnelle Ratifizierung in 2016 zeugen von einer starken Dynamik im weltweiten Vorgehen gegen die Erderwärmung. Da die globalen Treibhausgasemissionen bis zur Mitte des Jahrhunderts gegen Null gesenkt werden müssen, steht die schnelle Dekarbonisierung in vielen Ländern ganz oben auf der Tagesordnung. Diese Publikation gewährt Einblicke in die aktuelle Forschung im Bereich der Entwicklung hin zu kohlenstoffarmen Gesellschaften und soll damit zur Politikgestaltung auf internationaler sowie nationaler Ebene beitragen. Die in mehr als 20 präzisen Originalartikeln diskutierten Themen gehören zu den wichtigsten Fragestellungen, die zur erfolgreichen Bekämpfung des Klimawandels und zum Erreichen nachhaltiger Entwicklung beantwortet werden müssen. In den Beiträgen werden neue Erkenntnisse und Fallstudien aus folgenden Themenbereichen diskutiert: Steuerung langfristig notwendiger Veränderungsprozesse im Kontext bekannter sowie unerwarteter gegensätzlicher Entwicklungen ; politische Maßnahmen und Strategien zur Finanzierung der Übergänge hin zu kohlenstoffarmen Gesellschaften, welche gleichzeitig aktuelle wirtschaftliche und soziale Herausforderungen adressieren sowie ; integrierte Strategien für drei Bereiche, die für das Erreichen einer globalen Dekarbonisierung wesentlich sind: Städte, da der Wandel hin zu kohlenstoffarmen Gesellschaften sowie die dafür benötigten Investitionen zu einem großen Teil hier stattfinden sowie geplant, finanziert und umgesetzt werden müssen; Industrie, vor allem die energieintensive verarbeitende Industrie, die im Mittelpunkt des gesellschaftlichen Stoffwechsels steht und für einen großen, wachsenden Anteil der globalen Emissionen verantwortlich ist und Wissenschaft, die lösungsorientierter arbeiten sollte, da die benötigten Veränderungsprozesse stark auf wissenschaftliche Ansätze zur Lösung technologischer sowie gesellschaftlicher Probleme angewiesen sind. Als Beitrag zur Bewältigung dieser Herausforderungen und auf Wunsch der G7-Umweltminister dient das Low Carbon Society Research Network (LCS-RNet) als Forum zur Förderung von Forschung und Politikgestaltung mit dem Ziel kohlenstoffarmer Gesellschaften. Es bringt führende Wissenschaftler(innen), Fachkräfte und politische Entscheidungsträger(innen) zusammen und soll Regierungen bei der gemeinsamen Gestaltung und Umsetzung klimafreundlicher, kohlenstoffarmer Gesellschaften unterstützen.
urn:nbn:de:bsz:wup4-opus-66360
Keywords: 330